The Number of CD4+ T Cells on HIV/AIDS Patients who Have Received ARV Therapy - Adrianus Olawuan; Ni Ketut Yuliana Sari; Novian Agni Yudaswara; Neny Foekh; Arista Day Atajama (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Human immunodeficiency virus (HIV) is an infection that attacks the body’s immune system, specifically the white blood cells called Lymphocytes CD4+ T cells. Antiretroviral therapy is the main treatment used in the management of HIV / AIDS. Antiretroviral therapy proved able to suppress viral replication and increase the number of CD4 T-cells so as to suppress the progression of the disease. CD4+ T cell counts is an important indicator to determining the level of immunity of the human body, maintaining the number of CD4+ T cells in normal limits to defend themselves from complications related to HIV/AIDS in particular to prevent opportunistic infections. The number of CD4+ T cells will determine when people living with HIV should begin antiretroviral therapy. To determine the immune status and disease progression in a person infected with HIV, a CD4+ T cell count is performed. Without antiretroviral (ARV) therapy, most people living with HIV/AIDS (PLWHA) will become progressively immunodeficient, which is characterized by a decrease in the number of CD4+ T cells, then progresses to AIDS and can end in death. The purpose of this study was to describe the number of CD4+ T cells in HIV/AIDS patients who had received ARV therapy at Prof. Hospital. Dr. W.Z. Johannes Kupang. Descriptive observational analysed data from medical record of HIV/AIDS patients with antiretroviral therapy. A Total 100 patients who were eligible included in the study had both a CD4 lymphocyte CD4+ T cell count during 2020-2021. The average difference before and after therapy using Test with p-value 0.000 (p-value <0.05) indicates that there is a significant difference between the number of Lymphocytes CD4+ T cells counts before and after therapy.